Mutations in AXIN2 gene as a risk factor for tooth agenesis and cancer: A review - Hlouskova, Alena; Bielik, Peter; Bonczek, Ondrej; Balcar, Vladimir J; Šerý, Omar (Neuro endocrinology letters, 2017)
AXIN2 gene plays a crucial role in morphogenesis of craniofacial area and is essential for tooth development. AXIN2 gene is one of the most studied genes associated with tooth agenesis, the most common defect of dentition in humans. Polymorphic variants in AXIN2 gene are discussed in relation to the occurrence of the tooth agenesis but also as an indication of the risk of cancer. Mutations in AXIN2 gene were found in patients with colorectal or hepatocellular carcinoma, prostate cancer, ovarium or lung cancer. These findings support the hypothesis that missing teeth may be a significant marker for predisposition for cancer.
Keywords: mutace; rizikové faktory; Neoplasms; axin protein; nádory; Risk Factors; lidé; Genotype; Axin Protein; genotyp; Polymorphism, Genetic; Anodontia; Mutation; genetická predispozice k nemoci; polymorfismus genetický; Genetic Predisposition to Disease; anodoncie; Humans